Celik Arab: Aplikasi Pembelajaran Bahasa Arab Secara E-Learning bagi Kanak-Kanak Pra-Sekolah - Abdul Azim Ab Malik,; Mohamad Firdaus Ab Aziz, (Applied Information Technology And Computer Science, 2021)
Abstract: Celik Arab is an E-Learning Arabic Language Learning Application for Pre-School students developed to help children, especially students of Pusat Asuhan Tunas Islam (Pasti) in learning Arabic. This application is developed for students so that they can have learning experience using M-Learning application. Nowadays learning process was using face-to-face learning methods and difficult to implement it if some problem occurs such as virus Covid-19 pandemic. In addition, learning process is done using printed materials and has limitations of use where it can only be used once such as exercise books and requires other prints to do the next exercise. With the help of this application, students can do learning by using blended learning method which is learning through application without the presence of a teacher and can use the application anywhere and anytime with functions provided in the application as long as connected with internet. In addition, cost savings can be applied where there is no need to print materials for students to do exercise. The development of this application is based on the Agile model methodology which includes several phases which is planning phase, design phase, development phase, test phase, launch phase and feedback phase. The software used in application development is Android Studio and the database used is Firebase. There are several modules in this application such as administrator module, Arabic introduction module, basic Arabic learning module (simple dictionary) and training/ quiz module. Few functions such as navigation buttons, audio and graphics are also included in the application. It is hoped that this application is expected to help students, especially Pasti’s students as an alternative learning tool that has the characteristics of dynamic and intellectual interaction in its content.